Strategi Mencapai Penghidupan Berkelanjutan Pada Sektor Pariwisata Suku Tengger di Taman Nasional Bromo Tengger Semeru - Irsyad, Muhammad; Irwan, Siti Nurul Rofiqo; Budiani, Sri Rahayu (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2020)
Sustainable livelihood is a concept achieved through strategies for utilizing livelihood assets natural, human, social, physical, and financial (DFID, 2001; Scoones, 2009; and Ellis, 2000). The Tengger tribe of Ngadas Village in Bromo Tengger Semeru National Park area (TNBTS) earns income from the agriculture and tourism sectors. Vulnerability due to natural disasters, trend changes in tourist arrivals, and climate change affect the five livelihood assets and livelihood strategies. The objective of this study is to analyze the five livelihood assets owned and to identify livelihood strategies. The descriptive qualitative method is used to assess five livelihoods by weighting and scaling. Livelihood strategies are analyzed by using interactive analysis method with primary and secondary data obtained. The results reveal that natural asset provides the highest value of financial asset, supported by social asset and physical asset. Human asset has the lowest value compared to other assets. The consolidation strategy is the dominant strategy done by dividing works between family members, hiring laborers, and using financial reserves. Other strategies are also carried out through opening a tourism business, planting new agricultural crops, maintaining the environment and culture from damaging external influences.